Increased prevalence of vegetarianism among women with eating pathology. (December 2015) - Zuromski, Kelly L.; Witte, Tracy K.; Smith, April R.; Goodwin, Natalie; Bodell, Lindsay P.; Bartlett, Mary; Siegfried, Nicole
Abstract: Objective: Prior research has established a link between vegetarianism and disordered eating but has typically sampled vegetarians. This study examined prevalence of and variables related to vegetarianism in three samples with varying severity of eating pathology. Method: Sample 1 consisted of female undergraduates who denied history of or current disordered eating (i.e., nonclinical; n = 73), or engaged in disordered eating over past month (i.e., subclinical; n = 136). Sample 2 included 69 female patients receiving residential treatment at an eating disorder center (i.e., clinical sample). Differences between groups were analyzed using Fisher's exact test. Results: The prevalence of lifetime vegetarianism was lowest in the nonclinical group (6.80%) and highest in the clinical group (34.80%), with the subclinical group falling in between (17.60%). According to Fisher's exact test, all pairwise comparisons between groups were statistically significant ( p 's < .05). Regarding current vegetarian status, the clinical group was more likely (11.10%) than both other groups to self-identify as current vegetarians. Discussion: Endorsement of vegetarianism was highest among females with severe eating pathology. Future research should use longitudinal data to examine the temporal relationship between these variables, or other underlying factors that may contribute to the co-occurrence of eating pathology and vegetarianism. Clinically, endorsement of vegetarianism may also be an important variable to consider in treatment disordered eating.